Reduced Order Modeling for Direct Time-Response Analysis Using the Enhanced Craig–Bampton Method - Seung-Hwan Boo; Cheolgyu Hyun; San Kim; Chaemin Lee (Mathematics)
The increasing demand for dynamic analysis of large-scale structural systems has highlighted the need for efficient model reduction methods. Reduced order modeling allows large finite element models to be represented with significantly fewer degrees of freedom while retaining essential dynamic characteristics. This paper investigates the Enhanced Craig–Bampton (ECB) method and further explores its application in dynamic analysis. The effectiveness of the ECB method is evaluated by comparing it with the conventional Craig–Bampton (CB) method and the full finite element model using benchmark examples. The numerical results demonstrate that the ECB method provides superior accuracy and computational efficiency, making it a valuable tool for dynamic analysis in complex engineering problems.